ASME/BATH 2015 Symposium on Fluid Power and Motion Control 2015
DOI: 10.1115/fpmc2015-9600
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Mitigation of Valve Switching Losses in Switched Inertance Converters

Abstract: Switched inertance converters use digital valves to exploit the inertia of a flow in order to trade flow for pressure or vice versa. These components can be used to efficiently match load and supply pressures, avoiding the energy wasted by using resistive valves. While theoretical switched inertance converters can be highly efficient, practical implementations suffer from a number of energy losses. One of these losses is the valve switching loss: the energy wasted due to the flow experiencing a pressure drop a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Transmission lines of arbitrarily changing cross section can be modelled using this approach by successively connecting multiple tapered transmission line segments together. Using shaped inertance tubes has theoretically shown an increase in efficiency over using uniform tubes [8], and by applying this model, higher accuracy and speed in these simulations are expected. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission lines of arbitrarily changing cross section can be modelled using this approach by successively connecting multiple tapered transmission line segments together. Using shaped inertance tubes has theoretically shown an increase in efficiency over using uniform tubes [8], and by applying this model, higher accuracy and speed in these simulations are expected. …”
Section: Discussionmentioning
confidence: 99%
“…The approximate transmission matrix they derived was taken further in [6] by applying modal analysis (MA) and rational polynomial transfer function approximations (RPTFA) of the transcendental functions in the solution, allowing for simulations to be performed in the time domain. No further research into modelling tapered lines has appeared in the literature until this point, and the need for a robust, fast, and accurate model for tapered transmission lines has heightened with the growth in switched inertance converter research [8]. This paper will look at modelling tapered fluid lines using the TLM model and optimization procedure similar to that in [3] where weighted transfer functions make up the E, F, and G transfer functions.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Wiens et al modelled and quantified the switching loss for an HBC and suggested that a shaped inertance tube and a tank-flow valve positioned along the tube could reduce the switching loss. The methods were investigated in simulation, and showed increased volumetric and energy efficiencies [40,41]. In 2018, the team proposed an improved transmission line model (TLM) for a tapered tube by optimising the weighting functions of conventional TLM models [23].…”
Section: Load Inertance Tubementioning
confidence: 99%
“…Similarly, the orifice opening area of a flow-controlled rotary valve was derived by Okhotnikov et al, 20 and the flow characteristics and pressure loss characteristics of the rotary valve were studied. The pressure drop and local loss before and after the pilot control ball valve (PCGV) at different inlet velocities were analyzed by Jin et al 21 When the digital valve was switched from one position to another, the switching loss caused by the flow pressure drop through the valve was quantified by Wiens et al 22 The rapid rotation of the rotary valve port will cause the instantaneous change of the pressure difference, so the cavitation phenomenon and the influencing factors were analyzed by Lu et al 23 In addition, the crevice flow caused by the unsteady movement of the valve spool was also studied.…”
Section: Introductionmentioning
confidence: 99%